The chiton fauna (Mollusca: Polyplacophora) of South Africa - Erasmus, Karlien (Department of Biological Sciences, 2025)
Chitons are a diverse class of molluscs inhabiting marine waters and constitute a significant, yet relatively underexplored group of invertebrates in South Africa. Over the past three decades, taxonomic research has resulted in a pronounced increase in the description of regional chiton species, with the result that the most recent (1985- 2006) series of global monographs on chitons by Kaas and Van Belle now cover only 22 of the 50 chiton species currently recognised from the region, highlighting the need for a new synthesis of the fauna. This dissertation documents all the known chiton species inhabiting South African waters and adds new records of species that were previously undocumented. The study identifies an additional eight species new to the region from South African museum collections. A remarkable endemism is found in this group, with 46% of chiton species in South Africa found nowhere else. Of these endemics, 34% can be found only on the South Coast. The dissertation also includes a complete species list of the region and a user-friendly field guide that highlights key taxonomic features of the region's chiton species, with an accompanying binomial key for identification of species. It includes photographs and illustrations to aid in species identification, as well as a distribution map for each species. Chitonida is the largest order found in the region, with Acanthochitonidae, Chaetopleuridae, Chitonidae and Ischnochitonidae as four of the largest families in the region. Leptochiton is the most diverse genus in the region, also indicating a relatively high species richness in deeper waters. Chiton species of the region exhibit a greater species richness to the east and a higher endemicity to the South, with 56% of the species found on the South Coast endemic, though there seem to be a low intensity of collection on the Eastern coast. Although this dissertation adds significantly to the regional chiton fauna, further sampling and research is needed to comprehensively resolve and describe all the species and to assess their conservation status, given the anthropogenic threats these species face, including habitat destruction and possible unethical and unregulated collections.